FORMULATION DEVELOPMENT OF A PREGNANCY SUPPLEMENT BASED ON TUNA EYE OIL USING MIXTURE DESIGN: PENGEMBANGAN FORMULASI SUPLEMEN KEHAMILAN BERBASIS MINYAK IKAN MATA TUNA MENGGUNAKAN MIXTURE DESIGN - Wini Trilaksani; Silva Fauziah; Utami Dyah Syahfitri; Bambang Riyanto (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Stunting is a chronic nutritional problem with a high prevalence in Indonesia, with inadequate intake of protein and DHA during pregnancy being among the primary causes. This study aims to develop and optimize a pregnancy supplement formulation based on tuna eye oil and katsuobushi protein hydrolysate using a mixture design approach. The research stages included the extraction and characterization of fish oil from tuna eyeballs, the enzymatic hydrolysis of katsuobushi protein using papain, and the formulation of an emulsion using egg yolk as the emulsifier. Optimization was conducted using a simplex-lattice {3,1} design with axial points via Minitab 19 software. The optimal formulation consisted of 40.40% tuna eye oil, 31.02% katsuobushi protein hydrolysate, and 28.58% egg yolk, resulting in a pH of 4.29 and a viscosity of 3,880 cPs. The final product delivered 210 mg DHA per day, fulfilling the recommended daily intake for pregnant women. Nutritional profile and microbial safety tests also met established standards. These findings highlight the potential of tuna eye oil and katsuobushi-based supplements as an innovative nutritional intervention for stunting prevention.